Human or Inhuman? A Cyborg-Woman from the Novel by Dino Buzzati - Bartkowiak, Joanna (Sensus Historiae, 2020)
A gifted professor constructs a combat machine at a secret military base. He equips a cyborg with human traits; personality, emotions and memories of his deceased wife. Numero Uno, known as ‘Laura’, is the heroine of the precursory novel entitled Il Grande Ritratto published by Dino Buzzati in 1960. In this article, I try to extract her human and inhuman features and try to place this into a post or transhumanist concept. I consider the balance of these traits, taking into account the author’s relationship to the essence of humanity, of which he spoke about in interviews.